1999
DOI: 10.1074/jbc.274.7.4220
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Neuropsin, a Hippocampal Protease Involved in Kindling Epileptogenesis

Abstract: Neuropsin is a novel serine protease, the expression of which is highly localized in the limbic areas of the mouse brain and which is suggested to be involved in kindling epileptogenesis and hippocampal plasticity. The 2.1-Å resolution crystal structure of neuropsin provides the first three-dimensional view of one of the serine proteases highly expressed in the nervous system, and reveals a serine protease fold that exhibits chimeric features between trypsin and nerve growth factor-␥ (NGF␥), a member of the ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 29 publications
1
57
1
Order By: Relevance
“…Indeed, recombinant hK7 and the mouse ortholog of hK8 (mK8) were previously shown to be activated by Lys-C (Hansson et al, 1994;Shimizu et al, 1998). Furthermore, crystallographic studies of the kallikreins hK1, hK6 and mK8 revealed very similar structures (Kishi et al, 1999;Bernett et al, 2002;Gomis-Ruth et al, 2002;Laxmikanthan et al, 2005). From sequence analysis of other kallikreins, it is believed that all of them share a very close ternary structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, recombinant hK7 and the mouse ortholog of hK8 (mK8) were previously shown to be activated by Lys-C (Hansson et al, 1994;Shimizu et al, 1998). Furthermore, crystallographic studies of the kallikreins hK1, hK6 and mK8 revealed very similar structures (Kishi et al, 1999;Bernett et al, 2002;Gomis-Ruth et al, 2002;Laxmikanthan et al, 2005). From sequence analysis of other kallikreins, it is believed that all of them share a very close ternary structure.…”
Section: Discussionmentioning
confidence: 99%
“…As described for these proteases, increased hK8 activity may be caused by stabilization of the enzyme structure induced by Ca 2q binding. Amino-acid sequence alignment of trypsin, mK8 and hK8, and structural comparison of trypsin and mK8 Kishi et al, 1999) showed no insertions or deletions within the Ca 2q -binding loop region among these enzymes. Using structural analysis of trypsin complexed with Ca 2q (Bode and Schwager, 1975), it was shown that this ion associates with five amino acids on a loop of trypsin with five coordinate bonds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This protein may have orthologues in mouse, rat, and monkey (28 -31). It is distinct from neuropsin (KLK8), a hippocampal protease involved in kindling epileptogenesis in mice (32). Like the other members of the human kallikrein family, the KLK6 gene lies at chromosome locus 19q13.4, telomeric to the PSA (KLK3) and KLK2 genes (5,21).…”
mentioning
confidence: 99%